2015
DOI: 10.1016/j.urology.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Prostate Biopsy: Lessons Learned Midst the Evolution of a Disruptive Technology

Abstract: Lessons learned during a 6-year experience with more than 1200 patients undergoing targeted prostate biopsy via MRI/US fusion are reported: (1) The procedure is safe and efficient, requiring some 15–20 minutes in an office setting; (2) MRI is best performed by a radiologist with specialized training, employing a trans-abdominal multi-parametric approach and preferably a 3T magnet; (3) Grade of MRI suspicion is the most powerful predictor of biopsy results, e.g., Grade 5 usually represents cancer; (4) Some pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Complication rates are high for cystectomy and urinary diversion, especially in the frail elderly population with comorbidities [2]. Most studies are retrospective and the reported complication rates differ largely.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…Complication rates are high for cystectomy and urinary diversion, especially in the frail elderly population with comorbidities [2]. Most studies are retrospective and the reported complication rates differ largely.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In Figure 1 above, a falsely negative MRI from our institution is shown [2]. The MRI-invisible cancer is not a rarity.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…[43][44][45][46][47] Relatively recently, controlled trials have shown the relative value of in-bore versus systematic TRUS biopsies, and the success rates of image fusion targeted biopsies versus whole-mount histopathology and concomitant systematic biopsies. [48][49][50][51] The START protocol paper outlines the method by which these individual studies can be judged.…”
Section: Performance Metricsmentioning
confidence: 99%
“…In the SEER database at prostatectomy, 9.7% of cases were up-staged and 44% up-graded when comparing postoperative specimens with preoperative biopsies and clinical assessment [181]. Hopefully, as improved technology and methods develop, new approaches will more accurately characterise the disease [182]. In the SERPCR cohort the tumour had a very indolent course during the first years after diagnosis, but showed a gradual progression into more lethal cancer over the 20-year period.…”
Section: Discussionmentioning
confidence: 99%